Students' Operations of Evoked Concept Images in an Acid-Base Equilibrium System - SAGLAM, YILMAZ (Asian Journal of Chemistry, 2010)
This study confirms the cognitive process in which the students operated a variety of images associated with acid-base concept in an equilibrium system. Sixty two sophomore college students majoring in food science participated in the study in the year of 2007. The students received a questionnaire that involved open-ended items and consisted of 4 parts: (1) questions based on acid-base concept, (2) questions based on chemical equilibrium, (3) questions based on acidity and basicity of an equilibrium mixture, (4) questions based on acidity and basicity of a solution. The data indicated that 23 out of 62 students achieved an appropriate understanding of acid-base definitions and equilibrium concept. However, most students failed to interpret a united context, an acid-base equilibrium system. They operated a variety of inappropriate evoked concept images. To begin with, the students could not consider all their insight related to the problem. Rather, the new context, an acid-base equilibrium system, activated different portions of a concept image and they were mostly inappropriate. Second, while invoking a formal definition accurately, the students seemed to have an inappropriate concept image. Third, the students seemed to quite happily operate a concept image within a particular restricted context, but could not do so within a broader one. Finally, 2 conflicting evoked concept images emerged unconsciously and simultaneously without causing any cognitive conflict.